Quaternary Vegetation History of the Lower Bengal Basin (India) Inferred from Palaeo-palynological Analysis - Roy, Payel; Barui, Chandra (Annals of Tropical Research, 2015)
Black peat samples deposited in between sandy clay layers were collected from an uncovered profile at Rajarhat, 24 Paraganas (N), 20 km extreme North East of the city of Kolkata, (22⁰34’N, 88⁰ 30′ E) West Bengal. The profile resulted from an excavation made during the construction of a multistory building. Palynological investigations of the peat sample revealed a large deposits of pollen grains of mangrove species such as Heritiera, Excoecaria, Rhizophora, Sonneratia, Avicennia, Bruguiera, Nypa, Barringtonia, Phoenix paludosa, Aegiceras etc. Pollen grains of grasses, some freshwater plants, as well as fern spores (such as Acrostichum, Pteris, Pteridium and Polypodium) were also recovered in large quantities. All were found from a peat layer formed at a depth of about 5.35m to 6.14m from the surface. The fossil pollen assemblage found indicates the prevalence of a past typical mangrove vegetation, which is presently observed in the Sundarbans region (a mangrove swamps, about 85km south of greater Kolkata). The present study reflects a low lying landscape frequently transgressed by sea water and getting supply of fresh water from rivers. Ecological and edaphic factors such as increase of salinity, submergence, reclamation, flood etc. could have been responsible for any vegetation fluctuations.